Angelina's big city ballet - Holabird, Katharine (Holabird, Katharine. Angelina Ballerina., 2014)
Angelina goes to the most famous city in Mouseland to perform at the Big Cheese Dance Show with her cousin Jeanie, but the two clash over whether tap or ballet is better.